Breathing exercises - Alidina, Shamash (--For dummies., 2026)
Improve your life and health--one breath at a time. In Breathing Exercises For Dummies, mindfulness and breathwork teacher Shamash Alidina shares 150+ simple, science-backed techniques to help you reduce stress, sleep deeply, and boost focus and emotional well-being. From calming anxiety, to easing pain, and improving performance, these accessible exercises fit into everyday life, whether you're at work, at home, or on the go. Recommended by breath expert Patrick McKeown, this practical guide blends ancient wisdom with modern science to help you harness the power of your breath. No experience needed. Just breathe and begin.